Site on the vesicular stomatitis virus genome specifying polyadenylation and the end of the L gene mRNA. - Schubert, M (1980)
The 5'-terminal nucleotide sequence from positions 50 to 130 of vesicular stomatitis virus RNA was determined indirectly by using a defective interfering particle RNA which contains covalently linked genomic minus and antigenomic plus sense RNAs. The last 18 nucleotides of the L gene coding for in the viral polymerase were identified and isolated by specific duplex formation between 5' terminally labeled oligonucleotides from a small single-stranded defective interfering particle RNA and L gene mRNA. The L gene ends at position 60 from the 5' terminus of the vesicular stomatitis genome. The data demonstrated that the first seven adenine residues in the polyadenylic acid tail of L gene mRNA may be coded for in the genome and suggested that the viral transcriptase itself may carry out polyadenylation, possibly by chattering at the uridine-rich sequence at the end of the L gene. Analysis of the 5'-terminal sequence of vesicular stomatitis virus genomic RNA revealed that it might fold into a complex secondary structure with possibly 62% of the bases paired.